Celastrol inhibits chondrosarcoma proliferation, migration and invasion through suppression CIP2A/c-MYC signaling pathway - Jinhui Wu; Muchen Ding; Ningfang Mao; Yungang Wu; Chao Wang; Jiabin Yuan; Xiong Miao; Jingfeng Li; Zhicai Shi (Elsevier, 2017)
Chondrosarcomas (CS) is the second most frequent tumors of cartilage origin. A small compound extracted from Thunder God Vine (Tripterygium wilfordii Hook. F.) called celastrol can directly bound CIP2A protein and effectively inhibit cell proliferation and induce apoptosis in several cancer cells. However, little knowledge is concern about the important role of CIP2A in CS patients and the therapeutic value of celastrol on CS. Our results showed that CIP2A and c-MYC were verified to be oncoproteins by detecting their mRNA and protein expression in 10 human CS tissues by qRT-PCR and Western blots. After treatment of celastrol, the proliferation, migration and invasion were significantly inhibited; whereas the apoptosis was largely induced in human CS cell lines. In addition, celastrol inhibited the expression of CIP2A, c-MYC, and suppressed apoptotic proteins BAX and caspase-8 in human CS cells, on the other hand, it induced the expression of antiapoptotic protein Bcl-2. Finally, knockdown of CIP2A also inhibited the migration and invasion and induced apoptosis of human CS cells. To sum up, we found that celastrol had effects on inhibiting proliferation, migration, invasion and inducing apoptosis through suppression CIP2A/c-MYC signaling pathway in vitro, which may provide a new therapeutic regimen for CS.